2020
DOI: 10.1002/essoar.10504804.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supraglacial river forcing of subglacial water storage and diurnal ice sheet motion

Abstract: Surface melting impacts ice sheet sliding by supplying water to the bed, but subglacial processes driving ice accelerations are complex. We examine linkages between surface runoff, transient subglacial water storage, and short-term ice motion from 168 consecutive hourly measurements of meltwater discharge (moulin input) and GPS-derived ice surface motion for Rio Behar, a ∼60 km 2 moulinterminating supraglacial river catchment on the southwest Greenland Ice Sheet. Short-term accelerations in ice speed correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our previous field measurements during July 2015 found that regional and global climate models overpredicted Rio Behar runoff by +21-58% 8 . During a 6-13 July 2016 field experiment we revisited the site to collect a seven-day record of 168 consecutive hourly discharges 34 , concurrent with three-hourly ice surface lowering measurements from a network of ablation stakes installed near the gauging site (Methods and Figure S2). Shallow ice cores collected at the same site in July 2016 revealed that the bare-ice surface was porous and saturated with meltwater, with an average bare-ice density of just 690 kg m -3 within the upper 1.1 m of ice 26 .…”
Section: Climate Models Overestimate Meltwater Runoff On the Bare-ice Ablation Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Our previous field measurements during July 2015 found that regional and global climate models overpredicted Rio Behar runoff by +21-58% 8 . During a 6-13 July 2016 field experiment we revisited the site to collect a seven-day record of 168 consecutive hourly discharges 34 , concurrent with three-hourly ice surface lowering measurements from a network of ablation stakes installed near the gauging site (Methods and Figure S2). Shallow ice cores collected at the same site in July 2016 revealed that the bare-ice surface was porous and saturated with meltwater, with an average bare-ice density of just 690 kg m -3 within the upper 1.1 m of ice 26 .…”
Section: Climate Models Overestimate Meltwater Runoff On the Bare-ice Ablation Zonementioning
confidence: 99%
“…8 , two supraglacial lake catchments with satellite lake volume (SLV1 and SLV2) runoff estimates 12 , the Leverett Glacier (LG) catchment 42 , and the Akuliarusiarsuup Kuua River's northern tributary (AK4) catchment 48 sub-hourly measurements and associated quality measures were recorded. These raw data were converted to channel flow rate [m 3 s -1 ] in post-processing following data quality-control workflows optimized for the supraglacial environment 8,34 . The sub-hourly measurements were used to estimate ~±15 m 3 s -1 measurement uncertainty (error bars in Figure 1 representing one standard deviation in sub-hourly discharge).…”
Section: Implications For Sea Level Rise Predictionsmentioning
confidence: 99%